The Effect of Pharmacist Counseling on Knowledge of Hypertension Treatment: A Narrative Review - Amandha Baruni; Andika Nicholas Iqbal Ardiansyah; Anisa Rahayu; Nuning Nuning; Vallina Laurensia Indika Ningrum; Akhmad Azmiardi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Hypertension is a chronic condition that requires long-term medication adherence to prevent serious cardiovascular complications. Adequate knowledge about treatment is an important prerequisite for patients to achieve optimal adherence. Pharmacists play a crucial role in providing education and advice through medication counseling. Objective : This review aims to synthesize evidence narratively regarding the effect of counseling interventions conducted by pharmacists on improving patients' knowledge about hypertension treatment Research Methods/ Implementation Methods : This narrative review was conducted by tracing various relevant research articles. Article searches were carried out on the PubMed, Google Scholar, and ResearchGate databases, with publications from 2011 to 2022. The main keywords used included